Adaptasi Wajib Pajak Terhadap Coretax DJP Pada Masa Transisi 2025-2026: Netnografi Diskursus Publik Digital - Happy Tatemba; Harke Revo Leonard Polii (Community Engagement and Emergence Journal (CEEJ), 2026)
This study examines the adaptation of individual taxpayers (non-employees) and Micro, Small, and Medium Enterprises (MSMEs) to the implementation of the Directorate General of Taxes (DJP) Coretax system during the 2025–2026 transition period. The research employs a qualitative approach using netnography and qualitative content analysis of 48 purposively selected units of publicly available digital texts derived from official DGT documents, tax regulations, online news media, X/Twitter, YouTube, Instagram, and Facebook. The verified official data incorporated in this study include the pre-implementation phase (16–31 December 2024), the full implementation on 1 January 2025, the DJP official statement containing data as of 9 January 2025 at 18:55 WIB, the administrative sanctions relief policy under Decree KEP-67/PJ/2025, and data as of 5 March 2026 indicating that more than 6 million Annual Income Tax Returns (SPT) for Fiscal Year 2025 had been submitted, 15,268,493 Coretax accounts had been activated, and 12,514,829 individual taxpayers had registered for Authorization Codes/Electronic Certificates. The findings reveal three major themes: digital transition shock and procedural confusion, digital literacy gaps among non-employee individual taxpayers and MSMEs, and fluctuations in public trust toward the tax authority. The study demonstrates that technical difficulties do not occur in isolation; rather, they evolve into procedural uncertainty, encourage users to rely on informal learning resources and online tutorials, and ultimately influence trust in the DJP. The novelty of this article lies in its explanation of digital spaces as mechanisms of collective adaptation that operate through technical frictions, informal learning processes, and the reconstruction of trust during the adoption of digital taxation services. Practical implications include the need to strengthen user experience design, provide segmented digital literacy assistance, develop responsive risk communication strategies, and utilize digital spaces as valuable sources of policy feedback.